Implementasi Kurikulum Berbasis Masyarakat melalui Program 7 Poe Atikan di SDN 1 Tegal Munjul - Hasan, Nurfadillah; Aulia, Tatu Helsa; M, Ruhyat; Sianturi, Kristina Agnesia; Andalusia, Fairuz; Shalsabilla, Firliana Navani; Alindra, Afridha Laily (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Community-based curriculum is one of the innovations in the world of education that emphasizes the importance of collaboration between schools, families, and communities in the learning process. 7 Poe Atikan is one of the implementations of community-based curriculum. This study aims to see whether the 7 Poe Atikan program can improve the effectiveness of character education for students at SDN 1 Tegal Munjul Jaya. The study used a descriptive qualitative method with data collection techniques by distributing questionnaires to students, teachers, and guardians. As many as 73% of students stated that they knew enough about this program, then according to one of the teachers, this program also encourages students to learn about issues, culture, or potential in the surrounding community. The results of the questionnaire from guardians, as many as 60% of respondents stated that they were very knowledgeable about the 7 Poe Atikan program, while the rest, namely 40%, felt that they did not know much.